Epidemiology of amyotrophic lateral sclerosis in Friuli-Venezia Giulia, North-Eastern Italy, 2002–2014: a retrospective population-based study. Issue 1 (2nd January 2019) - Palese, Francesca; Sartori, Arianna; Verriello, Lorenzo; Ros, Silvia; Passadore, Paolo; Manganotti, Paolo; Barbone, Fabio; Pisa, Federica Edith
Abstract: Objectives : To describe the epidemiology of Amyotrophic Lateral Sclerosis (ALS) in Friuli-Venezia Giulia (FVG) region, Italy, over a 13-year period (2002–2014), estimating ALS (a) incidence, prevalence, and clinical features; (b) mortality, also comparing Udine municipality to the rest of FVG. Methods : We conducted a retrospective population-based study. ALS incident cases were ascertained using multiple sources and validated through expert review. We calculated crude and standardized incidence rate (IR), point prevalence and mortality rate (MR), each with 95% confidence interval. Standardized incidence (SIR) and mortality (SMR) ratio were calculated to compare Udine to FVG. Results : Among 444 incident cases (50.0% men, median age 68.5 years), onset was bulbar in 30.2%, spinal in 59.9%, mixed in 9.9%; 3.6% had familial ALS. Crude and 2000 European population standardized IR was respectively 2.81 (2.56–3.09) and 2.09 (1.89–2.29) per 100, 000 person-years. Standardized male-to-female incidence ratio was 1.05. IR peaked at age 65–74 years (men: 9.93, 8.04–12.32; women: 7.74, 6.18–9.67) and decreased thereafter. Prevalence was 8.36 (6.74–9.97) cases per 100, 000 inhabitants on 30 June 2009 and 7.98 (6.40–9.56) on 30 June 2014. SIR was 1.20 and SMR 1.11. Conclusions : When assessed over a long period, incidence of ALS was in the range of Italian and European population-based registries and showed a consistent pattern by age and sex. IR and MR were only slightly higher in Udine vs. FVG.